Activated sludge thermal hydrolysis for liquid fermentation to produce VFAs: Exploring the balance of carbon release between quantity, quality and recovery. (15th November 2022) - Liu, Hongbo; Dong, Lu; Zhang, Xuedong; Zhao, Cheng; Shi, Mingze; Li, Yajie; Liu, He
Abstract: Thermal hydrolysis has been widely applied to improve organics bioconversion during sludge anaerobic treatment currently, based on which, liquid fermentation to produce volatile fatty acids (VFAs) with high concentration and good purity has been successfully developed by only using hydrolysate as the substrate to avoid the interference of "useless" residual solids. Therefore, obtaining high-quality hydrolysate is the prerequisite for VFAs production via liquid fermentation. However, previous studies on sludge thermal hydrolysis either only focused on organics release or only on sludge dewatering. Actually, the quantity, quality and recovery of the carbon released from sludge are equally important, and a balance between them should be established. Results in the present study indicated that organics concentration in sludge hydrolysate could not be arbitrarily enhanced by increasing thermal hydrolysis intensity or sludge concentration, and interestingly there seemed a threshold of around 32 g/L that the highest concentration the sludge hydrolysate could reach. Moreover, with the increase of hydrolysis intensity, the bioavailability of sludge could be promoted but reached the maximum with BOD5 /COD of around 0.44 at 180 °C, while sludge dewaterability could be improved but also trended to stable after 160 °C. The findings of this study demonstrate that excessively high hydrolysis intensity would not only waste energy but also induce forms of non-biodegradable organics. The performances of sludge liquid fermentation, including VFAs production and sludge reduce, were closely related to hydrolysis intensity, the choice of which should be based on the balance of the quantity, quality and recovery of the released carbon. Graphical abstract: Image 1 Highlights: The upper threshold of organics concentration in hydrolysate was explored. Asynchronous variations of released carbon in quantity, quality and recovery were observed as hydrolysis intensity increas. Good performances of liquid fermentation was obtained in VFAs production and sludge reduce. Choice of hydrolysis intensity determined the economic benefits of sludge liquid fermentation process.